Tax-Aware Generation: Membentuk Kesadaran Perpajakan Siswa SMK Melalui Pembelajaran Interaktif Berbasis Digital - Rinaldi, Muhammad; Ariandi, Muhamad Amir; Fitria, Yunita; Ramadhani, Melda Aulia (Penerbit Goodwood, 2024)
Purpose: This community service activity aims to enhance students' understanding and awareness of taxation, specifically Personal Income Tax (PPh Articles 21 and 26). Methodology/approach: The activity was conducted at SMKN 2 Balikpapan, specifically targeting students in class XI AKL 1 on November 15, 2024. The methods used include interactive counselling, tax calculation simulations, group discussions, interactive training using the Quizizz application, and a satisfaction survey using Google Forms to evaluate the effectiveness of the program. Results/findings: The survey results indicated a high level of student satisfaction, with 76.7% of students being very satisfied with the materials and methods used. Students also demonstrated increased interest in taxation topics, although a few students still faced difficulties in understanding the technical aspects of tax calculations. Conclusion: This tax education activity was effective in increasing students' awareness and interest in taxation obligations. The interactive approach successfully improved student participation, although further simplification of the materials was required to ensure optimal understanding among all students. Limitations: The activity was limited to a single class at SMKN 2 Balikpapan, thus reducing its generalizability. Some students also had difficulty with tax calculations, suggesting a need for simplified materials. Contribution: This activity enhances tax literacy in vocational high schools by providing educators and policymakers with tools to improve student understanding and promote early tax compliance.